ZINC-ALPHA 2 GLYCOPROTEIN FACILITATES CATECHOLAMINE-INDUCED LIPOLYSIS IN HUMAN ADIPOCYTES THROUGH A CATALASE-LIKE EFFECT: FOCUS ON CARDIAC CACHEXIA. (June 2018) - Tedeschi, S.; Banti, L.; Graiani, G.; Poli, D.; Borghetti, A.; Perlini, S.; Cabassi, A.
Abstract : Objective: Cardiac cachexia development in heart failure is characterized by fat mass loss and elevated levels of circulating fatty acid (FA). Zinc alpha 2 glycoprotein (ZAG) has been demonstrated to induce lipolysis in vivo in rodents and in cardiac cachexia. We investigate ZAG mechanisms of action in human adipocytes obtained from healthy subjects (CTR), heart failure non cachectic patients (HFnCX) and cardiac cachectic patients (HFCX). Design and method: Two sets of experiments have been performed: in the first pilot study 6 CTR, 4 HFnCX and 3 HFCX subjects have been enrolled. Subcutaneous adipose tissue sample has been obtained during dermatological surgical procedure or at the moment of ICD or PM generator change. Isolate mature adipocytes were incubated with ZAG 25 ug/mL. H2O2 release in culture medium was evaluate before and after 1 and 2 hours of ZAG-incubation. Adipocytes have been also incubated with Norepinephrine (NE) 10-5 M, H2O2 10-4 M and 10-5 M and BRL44408 10-5 M (Selective alpha2A-adrenoceptor antagonist). Infranatant glycerol was measured as an index of lipolysis. In the second set of experiments 16 CTR, 19 HFnCX and 12 HFCX patients have been enrolled. Adipocytes were incubated with ZAG 25 ug/mL, Benzylamine (BZ) 1 mM and Tyramine (TY) 1 mM in different combination and H2O2 production was measured. Results: ZAG did not increased lipolysis but co-incubation with noradrenaline resulted in higher glycerol release in HFCX vs noradrenaline alone (+60%, p < 0.05). ZAG reduced H2O2 release from adipocytes to a greater extent in HFCX (+65%, p < 0.05) whitin the first hour of incubation. H2O2 incubation with adipocytes did not reduce glycerol release in the three group, nor reduced the NE-mediated lipolysis. H2O2 blunted the BRL44408-induced lipolysis when co-incubated with NE. A greater release of H2O2 from HFCX in basal condition and after incubation with BZ and TY was observed.ZAG reduced BZ-related H2O2 production in all the three groups, whereas TY did not. Conclusions: ZAG has a facilitating role in NE-induced lipolysis that could be linked to an antioxidant, reducing H2O2 levels especially in HFCX patients. ZAG reduced BZ-related semi-carbazide sensitive-oxidase H2O2 generation suggesting an involvment of this enzyme in its action.